PANKE, Luciana. Caminos para el protagonismo feminino. 1. ed. Valencia: Tirant Lo Banch, 2024. - Berger Pereira, Rafaela (Conexão Política, 2024)
PANKE, Luciana. Caminos para el protagonismo feminino. 1. ed. Valencia: Tirant Lo Banch, 2024.